The Influence of Brand Image and Product Quality on Purchasing Decisions - Sihotang, Charity Serepina; Supriyono, Supriyono (PT FORMOSA CENDEKIA GLOBAL, 2024)
Nowadays, people are interested in cafes, so it’s providing opportunities for business people to open and manage cafe businesses. Developments in the cafe business have made people choose modern cafes that suit their interests. This research was carried out to know the influence of brand image and product quality on purchasing decisions. Tanduk Cafe and Eatery is a cafe that has been around for quite a long time in Malang City. Online questionnaires were distributed to consumers of Tanduk Cafe and Eatery in Malang City using a non-probability sampling method with an accidental sampling technique. The sample in this study amounted to 78 respondents. This research shows the results of data processing using PLS. From the research results it can be concluded that brand image and product quality have a positive and significant influence on purchasing decisions.